Causal Context Presented in Subsequent Event Modifies the Perceived Timing of Cause and Effect - Umemura, Hiroyuki (Frontiers in Psychology, 2017)
The effect of perceived causality on other aspects of perception, such as temporal or spatial perception, has interested many researchers. Previous studies have shown that the perceived timing of two events is modulated when the events are intentionally produced or the causal link between the two events was known in advance. However, little research has directly supported the idea that causality alone can modulate the perceived timing of two events without having knowledge about causal links in advance. In this study, I used novel causal displays in which various types of causal contexts could be presented in subsequent events (movement or color change of objects). In these displays, the preceding events were the same (ball falling from above), so observers could not predict which subsequent events displayed. The results showed that the perceived causal context modulated the temporal relationship of two serial events so as to be consistent with the causal order implied by the subsequent event; ball hit the floor, then objects moved. These modulations were smaller when the movements implied preceding effect of the falling ball (e.g. wind pressure). These results are well suited to the Bayesian framework in which the perceived timing of events is reconstructed through the observers’ prior experiences, and suggest that multiple prior experiences would competitively contribute to the estimation of the timing of events.